An examination of raters' and ratees' preferences in process and feedback in performance appraisal - Manshor Amat Taap,; Kamalanabhan, T. J. (2000)
This paper examined the raters' and the ratees' preferences in Malaysia regarding the performance appraisal process and feedback. A total of 52 managers (raters) and 122 subordinates (ratees) participated. Analysis by t test and correlation showed significant differences between raters and the ratees on most factors. Ratees preferred to have more frequent appraisals than once a year and preferred to have more frequent feedback from the managers about their performance. Ratees' preference for the purpose of information on performance was towards salary increase, promotion, training, and career development whereas the raters gave more importance to training and career development.